Geographic Accessibility towards Primary Health Care in Karawang District - Ramadina, Nabila; Ardisasmita, Mulya Nurmansyah; Sujatmiko, Budi (UI Scholars Hub, 2021)
Health accessibility refers to the availability of health care services accessible to the community as required. However, the convenience of accessing such services vary throughout regions due to geography. Hence differences in geographic accessibility can be an obstacle to accessing health care. This study characterized the influence of geographic accessibility on primary health care (PHC) in Karawang District. A cross-sectional study was conducted in November 2019 in five sub-districts of Karawang District. Respondents were interviewed using questionnaires to collect geographic (mileage and travel time from respondents’ house to nearest PHC) and transportation (mode of transportation and transportation cost) data. In total, the study involved 513 randomly selected households, of which 11% had far to travel to the PHC, 22% had a long traveling time, and 23% had expensive transportation costs, with motorcycles being the most common means of transport. Therefore, PHCs in several sub-districts in Karawang District are less accessible due to geographic barriers.